Application of Cold Smoked Chicken Technology to Increase Productivity of the Curah Leduk Chicken Farming Group, Banyuwangi - Aryanti Candra Dewi; Merry Muspita Dyah Utami; Dian Hartatie; M Ja'far Sodik; Muhammad Ilham Maskuri (Universitas Sebelas Maret, 2026)
The poultry group of Curah Leduk, Banyuanyar Village, Banyuwangi Regency has experience in raising and selling live chickens to collectors and traditional markets. However, their business is still limited to selling live chickens without any post-harvest processing, which restricts opportunities for value addition and causes around 10% of chickens to remain unsold due to low body weight. To address this issue, a program was introduced to develop smoked chicken products using cold smoking technology as a solution to utilize unsold chickens and expand market opportunities. This program applied cold smoking as a novel approach, replacing the commonly used hot smoking method with a low-temperature process. This method offers advantages such as better product texture, a more delicate flavor, and lower nutrient loss. The initiative aimed to improve the knowledge and skills of the poultry group through practical training in cold smoked chicken processing, reducing dependence on live chicken sales. The program was implemented through five main stages: coordination, socialization, direct practical training, evaluation, and mentoring. During processing, the cold smoking method resulted in an average weight loss of 6.1% due to evaporation of water and fat. All 15 participants showed a 100% increase in knowledge, particularly in calculating weight loss after training. Smoked chicken processing also increased product value by approximately 48.9% compared to fresh broiler chicken. The outcome showed that the activity improved participants’ understanding of production cost estimation and selling price calculation based on weight loss, while also developing their practical skills to independently produce smoked chicken products.